2017
DOI: 10.1002/adom.201700176
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Enhanced Nitrogen‐Doped Graphene Quantum Dot Emission by Single Bismuth Telluride Nanoplates

Abstract: The light–matter interaction between nitrogen‐doped graphene quantum dots (N‐GQDs) and bismuth telluride (Bi2Te3) nanoplates is investigated. A maximum of (2.9 ± 0.3)‐fold emission rate enhancement is observed at room temperature due to the coupling of N‐GQD emission with the breathing mode of surface plasmon of single Bi2Te3 nanoplates. The enhancement varies with different emission wavelengths and nanoplate diameters in accordance with results obtained through the dipole radiation power in the electromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…To verify the role of PS spacer layer in Purcell effect, we present in Figure S5 (Supplementary Information) the time-resolved PL measurements of 50-nm thick CsPbBr3 NC on gold film without PS spacer layer. We found that the fast decay component in this situation is very close to the instrument response function (IRF) of about 0.3 ns [23]. Coupled with the intensity decrease in Figure S1, it is seen that the fast decay rate is not attributed to Purcell effect, but to non-radiative loss instead.…”
Section: Resultssupporting
confidence: 64%
“…To verify the role of PS spacer layer in Purcell effect, we present in Figure S5 (Supplementary Information) the time-resolved PL measurements of 50-nm thick CsPbBr3 NC on gold film without PS spacer layer. We found that the fast decay component in this situation is very close to the instrument response function (IRF) of about 0.3 ns [23]. Coupled with the intensity decrease in Figure S1, it is seen that the fast decay rate is not attributed to Purcell effect, but to non-radiative loss instead.…”
Section: Resultssupporting
confidence: 64%
“…To verity the role of PS spacer layer in Purcell effect, we present in Figure S2 (Supplementary Information) the time-resolved PL measurements of 50-nm thick CsPbBr3 NC on gold film without PS spacer layer. We found that the fast decay component in this situation is very close to the instrument response function (IRF) of about 0.3 ns [22]. Coupled with the intensity decrease in Figure S1, it can be seen that the fast decay rate is not attributed to Purcell effect, but to non-radiative loss instead.…”
Section: Methodssupporting
confidence: 64%
“…In the FEM [22,27], the emission rate enhancement is calculated as the dipole power ratio between that within the plasmonic layer structures and that in the perovskite film only. The calculated |E|-field mappings at resonances for ME and MEM structures with CsPbBr3 NC film are shown in Figure 4(c) and Figure 4(d), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, plasmonic nanostructures have been also reported for controlling the emission rate [48][49][50][51]. Compared to dielectric material with small radiative loss, the plasmonic material may give much larger spontaneous emission enhancement but with large radiative loss of plasmons [56][57][58][59].…”
Section: Controlling Spontaneous Emission Rate Through Local Density mentioning
confidence: 99%